Drying Accelerators to Enhance Processing and Properties: Ethanol, Isopropanol, Acetone and Acetic Acid as Pre-treatments to Convective Drying of Pumpkin - Carvalho, Gisandro Reis (2020)
ABSTRACT Different drying accelerators were studied to improve vegetable drying: acetone (AC), ethanol (ET), isopropanol (ISO) and acetic acid (AA). Pre-treatments were performed by immersion of pumpkin cylinders. Convective drying was performed at 40 °C and air velocity 1 m/s. Different aspects were evaluated: drying kinetics, structural changes (microstructure and macrostructure), thermal profile and viscoelastic and rehydration behaviours. The microstructure was modified by pre-treatments, being more pronounced with AC and AA. Thinner cell walls, changes on turgor and extraction of components and air were reported, affecting the mass transfer. Moreover, the microstructural changes reinforced anisotropy and also affected the macrostructure, changing the viscoelastic behaviour. All pre-treatments resulted in a super-diffusive behaviour, decreasing the drying time from 9% (ISO) to 22% (AC). Possible relations were discussed among the compounds’ physical properties, sample temperature profile, drying kinetics and equilibrium moisture. Rehydration was improved by ET and ISO, but impaired by AA. Although AC accelerates drying, it did not affect the rehydration. The viscoelasticity reflected the structure and composition, with the pre-treatments with higher structure modifications (AA and AC) losing elastic properties. In conclusion, the pre-treatments with isopropanol and ethanol showed better results, improving drying and rehydration, and are thus recommended.